Makna Satire Tersembunyi dalam Iklan (Analisis Semiotika Roland Barthes pada Iklan A Mild Versi Bukan Main) - Stephen Jaufarry; Lusia Savitri Setyo Utami (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
This research discusses the hidden meaning of satire in the Bukan Main version of A Mild advertisement. Today many social problems occur in Indonesian society, such as violations of rules and ethics that have been established by the community. Regarding these social problems, A Mild's product made an advertisement with the title Bukan Main to insult the Indonesian people who violated the rules. Based on this background, this research's problem formulation is how the meaning of satire is depicted in the Bukan Main version of A Mild advertisement. The research objective is to find out and describe the satire's meaning in the advert A Mild version of not playing. The theoretical review used is advertising, semiotics, and satire. This study using a qualitative approach with Roland Barthes' semiotic analysis. The meaning of satire is obtained from a multilevel meaning; this idea is known as the